IMPLEMENTASI KOMBINASI AFFINE CIPHER DAN ONE-TIME PAD DALAM PENGAMANAN PENGIRIMAN PESAN - Ahmad Suhendri; Bayu Dwi Juniansyah; M Joko Priono; Dedi Darwis (Jurnal Informatika, 2018)
In an exchange of messages that occur offline and online is very vulnerable to the threat of information theft with a combination of Affine Cipher and One-time Pad is expected to secure a message that is difficult to solve from information theft (Cryptanalysis).Affine Cipher works by using the two integer and One-time Pad keys using keys that match the existing text and the key is randomly generated.The combination of two algorithms is expected to secure information and can return back to its original form (Plainteks), so as not to cause any data lost or excessive. Plainteks, Affine Cipher, Cipherteks, One-time Pad, Cipherteks, Plainteks.Keywords:  Cryptography, Affine Cipher, OTP.